Haemato-biochemical evaluation of chemotherapy in canine transmissible venereal tumour - Nazer, Aja Taj; Becha, B Bibin; Jayakumar, C; Unnikrishnan, M P; Devi, Suma-Thankachy Sreekantan-Thampi (The Indian Journal of Animal Reproduction, 2023)
The study was aimed at haematological and biochemical evaluation of chemotherapeutic response in canine transmissible venereal tumour (CTVT). Thirty-one CTVT confirmed dogs presented to University Veterinary Hospitals were categorised into three groups. The group I (n=13) dogs were treated with vincristine sulphate, while group II (n=9) and III (n=9) dogs were treated with vincristine along with ivermectin and cyclophosphamide respectively. Haemato-biochemical evaluations were performed on the day of presentation and at weekly intervals till complete tumour regression. The haemato-biochemical parameters like TEC, Hb, VPRC, TP, BUN, creatinine, albumin, globulin and ALT were within normal range. Significant differenceswere observed in DLC, TC, MCV, AST, ALP and bilirubin levels (p<0.05) during treatment. Various blood dyscrasias like leucocytosis was observed in group I and group II, and thrombocytopenia in group III. Highly elevated AST, ALP and bilirubin were observed in all three groups. But combination therapy with ivermectin was more efficient with fewer adverse effects and decreased treatment duration.